Governance and policy in sport organizations / Mary A. Hums - Hums, Mary A.; Kluch, Yannick; Schmidt, Sam (Samuel H.); MacLean, Joanne, 1959- (Routledge, 2023)
The fifth edition of this hugely successful textbook introduces readers to the power and politics of sport organisations. It explores the managerial activities essential to good governance and policy development, and looks at the structure and functions of individual organisations within the larger context of the global sport industry.